2005
DOI: 10.1523/jneurosci.4217-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Long-Term Potentiation of Intrinsic Excitability in Hippocampal CA1 Pyramidal Neurons

Abstract: The efficiency of neural circuits is enhanced not only by increasing synaptic strength but also by increasing intrinsic excitability. In contrast to the detailed analysis of long-term potentiation (LTP), less attention has been given to activity-dependent changes in the intrinsic neuronal excitability. By stimulating hippocampal CA1 pyramidal neurons with synaptic inputs correlating with postsynaptic neuronal spikes, we elicited an LTP of intrinsic excitability (LTP-IE) concurring with synaptic LTP. LTP-IE was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
179
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(196 citation statements)
references
References 66 publications
14
179
3
Order By: Relevance
“…Findings like these have led to the conclusion that de novo protein synthesis initiated by an experience is an important component of memories formed for that experience. However, other consequences of protein synthesis inhibition may also be important for causing amnesia, including abnormal neurophysiological activity (Agnihotri et al 2004;Xu et al 2005), gene superinduction, and apoptosis (cf. Routtenberg and Rekart 2005;Gold 2008;Radulovic and Tronson 2008;Routtenberg 2008;Rudy 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings like these have led to the conclusion that de novo protein synthesis initiated by an experience is an important component of memories formed for that experience. However, other consequences of protein synthesis inhibition may also be important for causing amnesia, including abnormal neurophysiological activity (Agnihotri et al 2004;Xu et al 2005), gene superinduction, and apoptosis (cf. Routtenberg and Rekart 2005;Gold 2008;Radulovic and Tronson 2008;Routtenberg 2008;Rudy 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several actions of protein synthesis inhibitors offer alternative accounts for amnesia produced by these drugs. These include cell sickness (Rudy et al 2006;Rudy 2008), activation of protein kinases and superinduction of immediate early genes (Radulovic and Tronson 2008), abnormal neural electrical activity (Agnihotri et al 2004;Xu et al 2005), and intrusion of neural ''noise'' that masks the primary changes representing memory formation (Gold 2006). Neural responses to inhibition of protein synthesis such as these may impair memory either secondary to or independent of interference with protein synthesis.…”
mentioning
confidence: 99%
“…It is important that this form of excitability changes does not require synaptic activation. This contrasts with studies where excitability changes occur alongside synaptic plasticity, often sharing the same biochemical pathways (Daoudal & Debanne 2003;Li et al 2004;Xu et al 2005). Such excitability changes are harder to unite with the scheme proposed here, as they seem to require Hebbian learning to take place simultaneously with excitability changes, whereas in the proposed scheme one follows the other.…”
Section: Discussionmentioning
confidence: 69%
“…During various phases of learning excitability can change dramatically in both cortical and hippocampal networks (Brons & Woody 1980;Moyer et al 1996;Giese et al 2001. ) In vitro studies have revealed changes in both pre-synaptic (Ganguly et al 2000;Li et al 2004) and postsynaptic (Daoudal et al 2002;Xu et al 2005) excitability after LTP protocols. A recent study, however, showed that an increase in the excitability can be induced solely by short periods of high activity, independently of synaptic activation (Cudmore & Turrigiano 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic excitability (IE) of neurons is defi ned as the ability to fi re APs with given certain synaptic inputs. Furthermore, in previous studies, the relationship between the summation of excitatory postsynaptic potentials (EPSPs) and AP firing has often been found to reflect the degree of IE [1][2][3][4][5] . In these studies, enhanced effi ciency of EPSP-AP coupling was demonstrated to be a typical property of neurons having high IE, which suggests a possible information-storage mechanism.…”
Section: Introductionmentioning
confidence: 99%